Snow Moon - Prudence Priest (Prudence Priest Collection of the New Age Movements, Occultism, and Spiritualism Research Library, 2017)
An original watercolor by Prudence Priest showing a coven circling at a full moon esbat.
Snow Moon (Watercolor)
An original watercolor by Prudence Priest showing a coven circling at a full moon esbat. 1 Electronic records. 1 scanned Watercolor painting (.tif, .jpg). 63.7 MB (66,855,117 bytes) bytes.
Keywords: Esbats; Art; Rites and ceremonies; Ritual; Visual materials; Watercolors; Witchcraft in art; Witches in art